INDUCED BREEDING OF SYSTOMUS SARANA (HAMILTON, 1822) UNDER CAPTIVE CONDITION - SARKAR, HIRAK; BHAKTA, DIBAKAR (Journal of the Inland Fisheries Society of India, 2021)
Systomus sarana (olive barb) locally known as 'Sar-punti' has commercial importance both as food fish and ornamental fish. The species is reported to be vulnerable in India and critically endangered in Bangladesh. The population of the species from natural water bodies of Tripura declined over the years due to various ecological changes and over exploitation. S. sarana were bred through induced breeding with 'Wova-FH' as inducing agent at Lembucherra, Government fish seed farm under Department of Fisheries, Government of Tripura. Five sets of experiments were conducted during the month of June-August 2013 to find out most suitable sex ratio and month for breeding in the State in respect of ovulation, fertilization and hatching rate. Single dose of injection was given with 0.4 ml and 0.25 ml per female and male respectively. The interval between injection and spawning was 6-9 hours. 100% ovulation was recorded for all the five set of experiments while highest fertilization rate was recorded at 93.15±5.55% and hatching rate (79.50±3.51%) when sex ratio was maintained at 1:1 in July (set IV). Hatching period was 14-17 hours at 29.85 ± 1.55 oC. The study would be beneficial for successful captive breeding of S. sarana in the north eastern State like Tripura.Key words: Induced breeding, Systomus sarana, Wova-FH, fertilization rate, hatching rate